DAMPAK IMPLEMENTASI SEKOLAH LAPANG PENGENDALIAN HAMA TERPADU (SLPHT) PADI TERHADAP PENGGUNAAN PESTISIDA - - Suharjono (Agrovigor, 2011)
The objectives of this research are  to study relations between IPM technology  pesticide use. The factors is education level, age, experience level and economic level of the farmers. This research is corelational research with an ex-post facto approach. The data were taken from 150 farmers that have been participate in FFS-IPM and 20 farmers non-FFS-IPM as a control. The data were tabulated by using frequency tabulation and analyzed by path analysis.The data that have taken and desciptive analyzed show that: (1) the level of knowledge on IPM and adoption for IPM of whole respondent FFS-IPM farmers is in low category (100%), furthermore the attitude toward IPM for the greater part of respondent of  FFS-IPM farmers is in medium category (92%). (2) the level of  pesticide use for the greater part of respondent of  FFS-IPM farmers is in low category (47,3%), while for the greater part of respondent of non FFS-IPM farmers is in high category (70%).Results of path analysis show that level of knowledge on IPM, economic farmers, and adoption rate of IPM have simultaneous and significantly effect on level of  pesticide use with contribution on 51,8%.